Indicators of university social responsibility as a challenge for educational quality: teacher perception - de Moraes Abrahão, Viviane; Vaquero-Diego, Maria; Beltrán Garcia, Eva (Journal of Management and Business Education, 2023)
Universities around the world play a key role in shaping the leaders of the future. It is therefore essential that, in the exercise of University Social Responsibility (hereinafter, USR), the teaching staff is actively involved in engaging students with the principles of social, economic, and environmental responsibility. The aim of this study was to analyze the perception, attitude, and participation of the teaching staff of a private Spanish university with respect to USR at its Madrid and Barcelona campuses. A total sample of 43 university professors from both campuses related to socially relevant subjects in business careers was selected to answer a 21-question questionnaire on USR. In general, the results show significant differences between professors at the Barcelona and Madrid campuses with respect to their perceptions of existing social responsibility practices at the university, as well as their own roles in education for sustainable development, highlighting the lack of promotion of specific actions within the subjects taught. This study, although with a reduced sample, is a first diagnosis that seeks to find the strengths and weaknesses of the current situation and provide an objective view. It is hoped that these data will be a starting point to increase the training and awareness of teachers in USR, increasing the number of teachers in the field.